MAKNA AKUNTANSI PERTANGGUNGJAWABAN YANG MELAMPAUI - Hanif Hanif (Jurnal Akuntansi, 2021)
The concept of responsibility accounting accompanies the concept of responsibility center which means that any authority given to a manager over a business unit must be accounted for by that authority, especially the authority in achieving financial targets, both revenue and expenses. The concept of responsibility center and responsibility accounting are management tools to ensure that the entrusted manager truly upholds the trust by exercising the given authority and must dare to take responsibility for that authority in the future. This concept also emphasizes that a manager cannot be held responsible by his superiors for more than the authority given to him. More than that, this concept aims not to let in the management of the organization, managers throw responsibilities at each other or "scapegoat" others to escape the responsibilities of the work unit they lead. One of the functions of accounting is a tool for financial accountability, indeed the study of responsibility accounting is part of the realm of management accounting, but in a broader sense, the financial accountability of public companies can also be called "public accountability accounting". In this section, the irony occurs, accounting as a financial accountability tool sometimes "slips" into a manipulation tool. However, research at the level of society-based economy practice seems to show that the light of responsibility accounting remains illuminating and can even be referred to as “beyond responsibility accounting", because accountability accounting is not only interpreted as a material aspect, not limited to accountability to interested parties but accountability is related to religious values, namely, all things in this world will be accounted for in the future to God. Keywords: responsibility accounting, responsibility center, authority, responsibility, trust, religiosity References: Anthony, Robert N., and V. G. (2007). Management Control Systems (12th ed.). Boston: McGraw-Hill/Irwin. Arief Suadi (1997), Sistem Pengendalian Manajemen Yogyakarta, BPFE Burrel, Gibson, Gareth Morgan (1994), Sociological Paradigms and Organizational Analysis, England Ashgate Publishing Limited. Blocher, E. J., Stout, D. E., Juras, P. E., & Cokins, G. (2013). Cost Management: A Stategic Emphasis (7th ed.). Mc Graw Hill. Chaniago, Hasril (2019).Kisah Hidup Haji Bustamam:Pendiri Restoran Sederhana. Yayasan Pustaka Obor Indonesia, 2019 Hanif. (2015a). Introducing Mato Based Profit-Sharing Accounting and its Synergy with Cooperative and Sharia. Procedia - Social and Behavioral Sciences, 211, 1223–1230. https://doi.org/http://dx.doi.org/10.1016/j.sbspro.2015.11.163 Hanif.(2015b). Management Control System Design: An Interpretive Ethnography. Procedia - Social and Behavioral Sciences, 211, 119–126. https://doi.org/10.1016/j.sbspro.2015.11.018 Hanif . (2015c). Pencarian Makna Dibalik Akuntansi Kewirausahaan Berbasis Kearifan Lokal. Jurnal Akuntansi Hanif. (2017). (Re)Konstruksi Akuntansi Keuangan Bagi Hasil Sistem Mato. Akuntansi Multiparadigma, 8(2), 1–15. Retrieved from http://jamal.ub.ac.id/index.php/jamal/article/view/505 Hanif, Ludigdo, U., Rahman, A. F., & Baridwan, Z. (2013). Memaknai Corporate Governance Berbasis Kearifan Lokal. In Seminar Nasional Akuntansi (SNA) (Vol. 16, pp. 4813–4835). Manado, Indonesia: Ikatan Akuntan Indonesia. Hanif, Ludigdo, U., Rahman, A. F., & Baridwan, Z. (2015). Akuntansi Bagi-Hasil Sistem Mato:Etnografi Bisnis Restoran Padang. Jakarta: Mitra Wacana Media. Hanif, H., Rakhman, A., & Nurkholis, M. (2019). Building a Concept of Entrepreneurial Control, 8(4), 1198–1206. https://doi.org/10.18421/TEM84-13 Hanif, H., Rakhman, A., & Nurkholis, M. (2019). Building a Concept of Entrepreneurial Control, 8(4), 1198–1206. https://doi.org/10.18421/TEM84-13 Hanif, H., Rakhman, A., & Nurkholis, M. (2018). New Productivity Concept Based on Local Wisdom: Lessons from Indonesia. J. Mgt. Mkt. Review, 3(3), 96-103. Hanif, H., Rakhman, A., & Nurkholis, M., Pirzada, Kashan. (2019b). Intellectual capital: extended VAIC model and building of a new HCE concept: the case of Padang Restaurant Indonesia. African Journal of Hospitality, Tourism and Leisure Hansen, D. R., & Mowen, M. M. (2005). Management Accounting (7th ed.). Singapore: Thomson South-Western. Hilton, R. (2008). Managerial Accounting: Creating Value in a Dynamic Business Environment (7th ed.). Boston: McGraw-Hill/Irwin. Retrieved from 978-007-126555-3MHID 007-126555-4 Jensen, M., C., & Meckling, W. (1976). Theory o f the firm: Managerial behavior, agency cost a nd ownership structure, Journal of Finance Economic 3:305-360, di -download dari http://www.nhh.no/for/courses/spring/eco420/jensen-meckling-76.pdf Kamayanti, Ari (2016). Metode Penelitian Kualitatif Akuntansi Pengantar Religius Keilmuan. Yayasan Rumah Peneleh Kaplan, Robert S, Norton, David P. (2001). The Strategy Focused Organization How Balanced Scorecard Companies Thrive in The New Business Environtment. Boston, Massachusetts: Harvard Business School Press.